2012
DOI: 10.1021/jz301628b
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Generation Efficiencies in One-Dimensional CdSe Heterostructures

Abstract: To better understand the role nanoscale heterojunctions play in the photocatalytic generation of hydrogen, we have designed several model one-dimensional (1D) heterostructures based on CdSe nanowires (NWs). Specifically, CdSe/CdS core/shell NWs and Au nanoparticle (NP)-decorated core and core/shell NWs have been produced using facile solution chemistries. These systems enable us to explore sources for efficient charge separation and enhanced carrier lifetimes important to photocatalytic processes. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 50 publications
1
84
1
Order By: Relevance
“…It was demonstrated that the quantum dots have the ability to store and donate multiple electrons to the adsorbed cobaloxime catalysts, playing a key role in improving the photocatalytic efficiency. Tongying et al reported that the core‐shell CdSe/CdS nanowires exhibited very high photocatalytic efficiency for hydrogen generation, which is thirty times higher than that of the bare CdSe nanowires 112. CdSe is the active species responsible for chemical reduction processes despite of the presence of a CdS shell on it.…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…It was demonstrated that the quantum dots have the ability to store and donate multiple electrons to the adsorbed cobaloxime catalysts, playing a key role in improving the photocatalytic efficiency. Tongying et al reported that the core‐shell CdSe/CdS nanowires exhibited very high photocatalytic efficiency for hydrogen generation, which is thirty times higher than that of the bare CdSe nanowires 112. CdSe is the active species responsible for chemical reduction processes despite of the presence of a CdS shell on it.…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…For example, CdSe NWs coated with 6 and 10 monolayers CdS exhibit PL quantum which increase from 0.14 % (uncoated) to 0.25 and 0.46 %, respectively [48]. As will be discussed later in this chapter, photocatalytic hydrogen generation efficiencies also increase due to enhanced carrier lifetimes [10].…”
Section: Synthesis Of Core/shell Semiconductor Nwsmentioning
confidence: 96%
“…CdSe/CdS NWs have likewise been made by decomposing CdMe 2 /(TMS) 2 S [49] or CdMe 2 /S powder [10] precursor pairs in a noncoordinating solvent such as squalane. Resulting shells appear rough and exhibit islanding (Fig.…”
Section: Examples Of Core/shell Nwsmentioning
confidence: 99%
See 2 more Smart Citations